Pink flamingos [videorecording (DVD)] - Waters, John, 1946-; Waters, John, 1946-; Divine, 1945-1988; Lochary, David, 1944-1977; Pearce, Mary Vivian; Stole, Mink (Warner Bros., 2017)
A criminal is hiding from the FBI in a trailer outside of Baltimore, Maryland. WARNING: Contains graphic images that some viewers might consider disturbing.